Transfer Gen Badh2 Termutasi Varietas Aromatik Mentik Wangi ke Varietas Nonaromatik Ciherang - Djarot Sasongko Hami Seno; Bambang Padmadi; Dewi Praptiwi; . Sugihartati; . Taufiq; Muhammad Taufan Fatahajudin; Helmy Ramadhan Al Anshary; Tri Joko Santoso; Zainal Alim Mas'ud (Jurnal Ilmu Pertanian Indonesia, 2011)
Replacement of non-fragrant-native badh2 gene with mutated badh2 of fragrant rice is an alternative to engineer new fragrant rice varieties with good agronomic traits as those of non-fragrant. Fragrant gene (mutated badh2) of Mentik wangi donor was introgressed into non-fragrant Ciherang host through site-directed crossing. Mentik Wangi was crossed with Ciherang, and the progeny was further backcross until BC3F1. Bradbury marka-assisted PCR was used to select progeny in every cross and backcross generation. Ciherang, Mentik Wangi, and their cross/backcross showed different PCR profiles. The statues of badh2 gene (native/mutated), as well as alleles (homozygote/heterozygote) between samples were identified. Mutated badh2-introgression was also observed within the selected heterozygote cross or backcross progenies (Fl, BCl, BC2, and BC3), indicated successful transfer of mutated badh2 gene from donor to host.